Electrospun nanofibrous scaffolds of segmented polyurethanes based on PEG, PLLA and PTMC blocks: physico-chemical properties and morphology - Bergamo Trinca, Rafael (2015)
Abstract Biocompatible polymeric scaffolds are crucial for successful tissue engineering. Biomedical segmented polyurethanes (SPUs) are an important and versatile class of polymers characterized by a broad spectrum of compositions, molecular architectures, properties and applications. Although SPUs are versatile materials that can be designed by different routes to cover a wide range of properties, they have been infrequently used for the preparation of electrospun nanofibrous scaffolds. This study reports the preparation of new electrospun polyurethane scaffolds. The segmented polyurethanes were synthesized using low molar masses macrodyols (poly(ethylene glycol), poly(l-lactide) and poly(trimethylene carbonate)) and 1,6-hexane diisocyanate and 1,4-butanodiol as isocyanate and chain extensor, respectively. Different electrospinning parameters such as solution properties and processing conditions were evaluated to achieve smooth, uniform bead-free fibers. Electrospun micro/nanofibrous structures with mean fiber diameters ranging from 600 nm to 770 nm were obtained by varying the processing conditions. They were characterized in terms of thermal and dynamical mechanical properties, swelling degree and morphology. The elastomeric polyurethane scaffolds exhibit interesting properties that could be appropriate as biomimetic matrices for soft tissue engineering applications.